O54 Randomised, double-blind, placebo-controlled study investigating enterosgel® treatment of irritable bowel syndrome with diarrhoea (RELIEVE IBS-D). (19th June 2022) - Yiannakou, Yan; Howell, Carol; Kemppinen, Anu; Allgar, Victoria; Dodd, Matthew; Knowles, Charles; McLaughlin, John; Pandya, Preeti; Whorwell, Peter; Khovanov, Alexander
Abstract : Introduction: Patients with irritable bowel syndrome with diarrhoea (IBS-D) experience abdominal pain and diarrhoea, with few treatment options. The intestinal adsorbent Enterosgel binds harmful molecules in the gut and can reduce diarrhoea (Howell CA, et al. BMJ Open Gastroenterol. 2019;6(1):e000287). Methods: This was a randomised multi-centre double-blind trial, eligible participants were randomised after a 2-week screening phase into an 8-week double-blind phase (Enterosgel or placebo), followed by an 8-week open-label phase and a follow-up phase (responders only). Subjects aged 16–75 years diagnosed with IBS-D (Rome IV criteria), reported stool consistency, pain and global symptoms in an e-diary and questionnaires. Primary outcome was percentage of responders for composite abdominal pain and stool consistency during at least 4weeks of treatment period. In the pandemic, the study opened a virtual site, using online screening questionnaires, e-consent and virtual visits. Results: The study ran from Nov 2018 to Oct 2021 randomizing 440 subjects (170 via virtual, 270 via GP/hospital sites) with 393 continuing to the open-label phase. Analysis by ITT for primary endpoint showed significantly higher percentage of treatment responders in the Enterosgel compared to the Placebo group (37.4 vs 24.3, Odds Ratio 1.95, NNT 7.6, p=0.002). Enterosgel also improved individual stool consistency (48.5% vs 32.5%) and abdominal pain scores (53.3% vs 40.2%), stool frequency, bloating and urgency. The open-label phase confirmed treatment effect was maintained in the active arm and improved in those previously allocated to placebo, with 60% of patients entering the study reporting adequate relief of symptoms at end of open-label. Treatment benefit was maintained during follow-up phase and of the 253 patients completing this phase, 203 (80%) chose to continue taking OTC Enterosgel. Safety analyses showed the treatment was safe. Conclusions: This study suggests Enterosgel is a safe and effective treatment of IBS-D, providing a valid alternative to the few treatment options currently available.